Analysis of Strong Female Characters in The Film I Am Rage (2023) Using Existentialist Feminism - Nurdilah, Nurdilah; Irma Rahmawati (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Existentialist feminism put forward by Simone de Beauvoir has become an important foundation in understanding the position of women in society and their representation in the media. In the context of the film I am rage (2023), this research aims to analyze strong female characters in the narrative, by applying key concepts from de beauvoir, such as ‘the other’ and the individual’s search for freedom. The film offers a complex depiction of women’s struggles and search for identity. amidst patriarchal norms. Through an analysis of the main characters, this research highlights how women are not only positioned as objects but also as active agents who confront and challenge restrictive social structures. By integrating de Beauvoir's theory, this finding suggests that despite progress in gender representation in film, the challenge of changing societal standards about women still needs to be faced. This study not only contributes to the understanding of feminism in the context of film, but also provides insight into the importance of representing women more authentically and diversely in the film industry.